Survey of economic conditions in Africa, 1970 - Economic Commision for Africa (New York : United Nations, 1971)
This survey of comic conditions in Africa for 1970 is concerned with national income accounting in Africa. It provides a comprehensive income data for African countries in the 1960s.
Part II
lje 12/4/19
Arch.
Keywords: Economic conditions; National Income; Africa